(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2019)
As we temporarily move away from the financial and banking crises of the first two decades of the twenty-first century, it appears that there has been much more than deregulation, subprime, and leverage of the international banking system. Today, faced with the slowness of the NPL’s “financial reorganization” process in banking, there is a deep feeling that structuring, and then almost invisible sequels are now much more difficult to overcome than the financial crisis itself. Why? For two essential reasons: In the first place, because these structuring aspects were and are intangible, it would almost be said to develop in a “subreal framework” to the current life of corporations. Then and as a consequence, their immediate perception is more difficult when the corporate decision focuses on overcoming the damages as the only operational way to recover corporate identity. Cultural values, symbolic culture and cultural behavior patterns are increasingly concepts outside the current operability of companies. For two complementary reasons: because they are not easily distinguishable from each other and because they are also inter-influenced which conditions their current feasibility. Key Words: Banking, Financial Crisis, Organizational Culture, Values, Short-Termism, Organization Behaviour, Risk Transformation.